Further enhancement of bicubic interpolation in image resampling - Amy G. Evangelio; Clarice M. Igat and Vien Jaimee S. Ramos. 4 0 16; 5 (2011)
u
Undergraduate Thesis: (BS in Computer Studies major in Computer Science) - Pamantasan ng Lungsod ng Maynila, 2011.
Keywords: 2 -- 0; 6; 20; 20; 2